42.9k views
14 votes
If r(x) = 3x - 1 and s(x) = 2x + 1, which expression is equivalent to

402
-
3(6)-1
2(6)+1
(6)
2(6) +
36-1
26+1
(6)-1
(6) +1

If r(x) = 3x - 1 and s(x) = 2x + 1, which expression is equivalent to 402 - 3(6)-1 2(6)+1 (6) 2(6) + 36-1 26+1 (6)-1 (6) +1-example-1
User CyberRobot
by
4.3k points

1 Answer

7 votes

Answer:

(3(6)-1)/(2(6)+1)

Explanation:

See attached image.

If r(x) = 3x - 1 and s(x) = 2x + 1, which expression is equivalent to 402 - 3(6)-1 2(6)+1 (6) 2(6) + 36-1 26+1 (6)-1 (6) +1-example-1
User Evgeni Roitburg
by
4.8k points